Development of communication configuration for mobile home security robot / Mohamad Farid Misnan - Misnan, Mohamad Farid (2009)
The Mobile Home Security Robot developed is designed for home security function. The Mobile Home Security Robot is aim to monitor and secure places at the home such as living room, kitchen, and master bedroom by utilizing a wireless RF interface and a GSM system to alert the owner if there is any breaking of the house. The wireless RF interface is used to transmit signals from the transmitter and transmit the command to control the status event of the house using RF wireless. When fire or thief breaking, the mobile robot can detect and transmits the information to the owner through GSM modem to inform of the incident.